Regional Data Centers as Catalysts for Sustainable Digital Pedagogy in Islamic Education: A Systematic Literature Review of Innovative Science Learning Models in Elementary Schools - Elihami Elihami; Mohammad Azis; Dafit Afianto (Pedagogy Review, 2026)
The rapid advancement of digital technologies has transformed educational systems worldwide, creating opportunities for innovative teaching, learning, and knowledge management. Nevertheless, disparities in digital access, infrastructure availability, and technological readiness remain significant challenges, particularly in Islamic elementary education. These challenges affect the quality of science learning and limit students’ ability to develop scientific literacy, digital competence, critical thinking, and other twenty-first-century skills. Therefore, this study aims to examine the role of regional data centers in supporting sustainable digital pedagogy and enhancing digital literacy through innovative science learning models in Islamic elementary schools. This study employed a Systematic Literature Review (SLR) to synthesize evidence from national and international scholarly publications on digital pedagogy, regional data infrastructure, Islamic education, and science learning innovation. The review included peer-reviewed journal articles, conference proceedings, policy papers, and academic reports published between 2015 and 2025. The collected literature was analyzed using thematic coding and content analysis to identify major trends, opportunities, and challenges associated with implementing regional data centers in educational settings. The findings indicate that regional data centers significantly improve digital accessibility, strengthen data security, support cloud-based educational services, and enhance the efficiency of learning management systems. Furthermore, innovative pedagogical approaches such as blended learning, inquiry-based learning, project-based learning, and artificial intelligence-assisted learning were found to improve students’ scientific understanding, digital literacy, problem-solving skills, and collaborative competencies. The study also reveals that regional digital infrastructure can reduce educational disparities between urban and rural schools by providing more equitable access to digital resources and learning platforms. In conclusion, regional data centers serve as strategic enablers of sustainable digital pedagogy and digital transformation in Islamic elementary science education. Strengthening collaboration among educational institutions, policymakers, technology providers, and local governments, along with sustained investment in digital infrastructure and teacher professional development, is essential for building inclusive, resilient, and future-oriented educational ecosystems.Keywords: Regional Data Centers; Digital Pedagogy; Islamic Education; Digital Literacy; Science Learning